Implikasi Perppu Cipta Kerja Terhadap Kesejahteraan Buruh: Tinjauan Ulang Dari Maqashid Syariah Jamaluddin Athiyyah - Dwi Rahayu, Hesti Maharani (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2025)
This research aims to analyze the impact of the Job Creation Perppu on workers' welfare from the perspective of Maqashid Syariah according to Jamaluddin Athiyya. Global employment issues, such as high unemployment, worker welfare, employment contracts, and layoffs, remain unresolved. Many acknowledge that workers often do not receive fair and equitable treatment. In the West, labor is seen as economic capital but is at times constrained. Workers should have the right to develop their potential and receive humane treatment. This study employs the library research method, gathering and analyzing relevant literature to discuss and draw conclusions. The analysis reveals that Islam regards all humans as having an equal standard of living, differing only in their level of devotion to Allah SWT, thereby entitling workers to prosperity. According to the maqashid of Sharia, Jamaluddin Athiyya stresses the importance of safeguarding honor (Hifdz al-'Irdli), property (Hifdz al-Mal), social justice (Iqamat al-'Adl), and supporting human rights. By granting workers the same rights as employers, justice can be established without injustice.